Phenolic Compounds Characteristic of the Mediterranean Diet in Mitigating Microglia-Mediated Neuroinflammation - Hornedo-Ortega, Ruth; Cerezo, Ana B.; de Pablos, Rocío M.; Krisa, Stéphanie; Richard, Tristan; García-Parrilla, M. Carmen; Troncoso, Ana M. (Frontiers in Cellular Neuroscience, 2018)
Neuroinflammation is a pathological feature of quite a number of Central Nervous System (CNS) diseases such as Alzheimer and Parkinson´s disease (AD and PD) among others. The hallmark of brain neuroinflammation is the activation of microglia, which are the immune resident cells in the brain and represents the first line of defense when injury or disease occur, leading to the microglia activation. Microglial activated cells can adopt different phenotypes to carry out its diverse functions. Thus, the shift into pro-inflammatory/neurotoxic or anti-inflammatory/neuroprotective phenotypes, depending of the brain environment, has totally changed the understanding of microglia in neurodegenerative disease. For this reason, novels therapeutic strategies which aimed to modify the microglia polarization are being developed. Additionally, the understanding of how nutrition may impact the prevention and/or treatment of neurodegenerative diseases has grown greatly in recent years. In this context, there is extensive evidence that demonstrates how the consumption of food based on the Mediterranean diet (MD) can bring health benefits, among them neuroprotection. This dietary pattern includes as distinctive features the moderate intake of red wine and extra virgin olive oil (EVOO), both of them rich in polyphenolic compounds, such as resveratrol (RV) and hydroxytyrosol (HT) and their derivatives, which have demonstrated anti-inflammatory effects on microglia. This review summarizes our understanding of the role of dietary phenolic compounds characteristic of the MD in mitigating microglia-mediated neuroinflammation.